Systematic Literature Review: Designing an Informatics Learning System Based on Gamification Concepts - Nenden Nurfadillah; Irdam Denni; Aceng Ahmad Rodian Susila (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Digital transformation in the field of education demands continuous innovation in learning processes, particularly in informatics courses that emphasize the mastery of computational thinking and programming skills. One widely developed approach is gamification, which refers to the integration of game elements into learning contexts to enhance students’ motivation and engagement. This study aims to analyze trends, dominant elements, platforms used, impacts, and future development directions of gamification-based informatics learning systems through a Systematic Literature Review (SLR) method. The research methodology follows the PRISMA guidelines, encompassing stages of literature identification, title and abstract screening, full-text eligibility assessment, as well as data analysis and synthesis. A total of 24 articles were identified in the initial search and subsequently selected based on predefined inclusion and exclusion criteria, resulting in 10 articles for in-depth analysis. The PICOS framework was employed to clarify the scope of the review, including informatics learners as the population, gamification as the intervention, conventional learning as the comparison, and outcomes in terms of motivation, engagement, and learning achievement. The findings indicate a significant increase in the implementation of gamification in informatics education over the past five years. The most dominant gamification elements identified are points, badges, levels, and leaderboards, with web-based e-learning platforms serving as the primary medium for implementation. Overall, gamification has consistently demonstrated positive effects on students’ motivation, engagement, and learning outcomes. This study concludes that gamification holds strong potential as an effective and sustainable learning strategy to support digital transformation in informatics education.